Daily life scenes depicted on a broken beam - Temples of India Project Team (Jio Institute, 2024)
It appears that the beam, adorned with intricately carved human figures, was probably placed on the varandika of the temple, the adjoining portions between the temple walls and the spire. The protruding offsets typically feature mithuna figures inside the niches, while the recess between the two offsets is beautifully carved with images of apsaras or women engaged in different actions. The male figures are usually shown with weapons and accompanied by female companions. This fragment is one of the loose architectural fragments on Harsha Hill.